Cystoporata (Bryozoa) del Carbonífero de la cuenca Tepuel-Genoa, Provincia del Chubut, Argentina (Ameghiniana, 2014)
Cystoporata from the Carboniferous of west central Patagonia are described for the first time in South America. Three species were assigned to Fistuiamina Crockford, of which two are new: Fisiulamina bifurcaia and Fistulamina amosi. They are comparable with Eastern Australian forms. Fistulaminafrondescens Crockford, known from the Upper Kuttung Series, Kullatine and Booral Forrnations, was also found in the Tepuel-Genoa Basin. The bryozoan specimens were found at sierra de Tepuel (Pampa de Tepuel Formation) and sierra de Languiñeo (Las Salinas Formation). The species belong to the Carboniferous Lanipustula Zone. It is during this time that faunal relations with Australia are so striking, and this is specially evident for the bryozoans. A comparative study shows that: five species are common and three are comparable to Eastern Australia and three genera are only present in Australia and Argentina. New types of morphologic structures are described and illustrated for the first time in Fistulamina Crockford.